DAMPAK COVID-19 TERHADAP PERMINTAAN DAN PENAWARAN COKELAT BATANGAN DI PTPN I DOESOEN KAKAO KENDENGLEMBU KARANGHARJO GLENMORE BANYUWANGI - Rizal, Mohamad; Prayuginingsih, Henik; Hadi, Syamsul (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Chocolate is a processed food product whose ingredients are a combination of chocolate paste, sugar, cocoa butter and several types of flavor additives. The Covid pandemic is predicted expected to affect the demand and supply of chocolate bars at Doesoen Kakao. The objectives of this research are 1. To find out whether there is a difference in demand for processed chocolate during and after COVID - 19 Doesoen Kakao Glenmore Banyuwangi, 2. To find out whether there is a difference in the supply of processed chocolate during and after COVID - 19 Doesoen Kakao Glenmore Banyuwangi. The research method used is descriptive and comparative analysis methods for secondary data, the sampling method uses convenience sampling using 6 months of data during the 2021 Covid pandemic and 6 months after the 2022 Covid pandemic. The research results show that: (1) There is an increase in demand for chocolate bars during Covid and after Covid but not significant, except for the White chocolate variant which experienced a decline in demand (2) There was an increase in offers of chocolate bars during Covid and after Covid but not significantly, except for the White chocolate variant which experienced a decline in supply.